Component analysis using UPLC-Q-Exactive Orbitrap-HRMS and quality control of Kudingcha (Ligustrum robustum (Roxb.) Blume). (December 2022) - Ling, Zhizhou; Zeng, Rong; Zhou, Xiangyuan; Chen, Fang; Fan, Qian; Sun, Dongmei; Chen, Xiangdong; Wei, Mei; Wu, Runsong; Luo, Wenhui
Graphical abstract: Highlights: A rapid method of identifying the general chemical components of Ligustrum robustum (Roxb.) Blume was established for the first time. The characteristic cleavage pathways of the phenylpropanoid, monoterpene, and flavonoid glycosides were comprehensively elaborated. There were significant differences in the characteristic compositions of phenylpropanoid and monoterpene glycosides between mature and young leaves of Ligustrum robustum (Roxb.) Blume. The mixing of mature and young leaves during harvest would lead to significant differences in quality stability. An unprecedented quantitative analysis of multi-components by single marker was set up to analyze the signature components. Abstract: Although Kudingcha ( Ligustrum robustum (Roxb.) Blume) has been widely used as both traditional medicine and food, systematic studies on their basic active components and quality control are lacking. In this study, a rapid method of identifying the general chemical components of Ligustrum robustum (Roxb.) Blume was established for the first time using UPLC-Q-Exactive Orbitrap-HRMS, and its major basic components were specified as phenylpropanoid, monoterpene, and flavonoid glycosides. The characteristic cleavage pathways of the phenylpropanoid, monoterpene, and flavonoid glycosides were further investigated and elaborated, which could assist in identifying the structures of similar components of other Chinese herbal medicines. A breakthrough was achieved in establishing a chemical fingerprinting profile of Ligustrum robustum (Roxb.) Blume from its original growing areas in China, and chemometric measures were applied to investigate the causes for the variations in its quality stability. The results indicated significant differences in the characteristic compositions of phenylpropanoid and monoterpene glycosides between mature and young leaves of Ligustrum robustum (Roxb.) Blume; however, no significant variation was observed owing to different production areas. Graded harvesting criteria should be established, and harvest period should be specified according to the target active components while considering agricultural metrics, such as leaf shape index, leaf length, and leaf width, to ensure the consistency in quality of active components during their production. From the perspective of overall quality control, an unprecedented quantitative analysis of multi-components by single marker was set up to analyze the signature components of phenylpropanoid glycosides (acteoside, isoacteoside, ligurobustoside N, and ligupurpuroside B) to increase the analytical efficiency and reduce research costs. This study created a scientific basis for the standardized operation, elucidation of the pharmacological materials, and quality control of food and supplements production with Ligustrum robustum (Roxb.) Blume as a raw material.